2022
DOI: 10.3389/fcvm.2022.932054
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin vs. heparin on a background of ticagrelor and aspirin in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention: A multicenter prospective cohort study

Abstract: ObjectiveCurrent guidelines recommend potent P2Y12 inhibitors such as ticagrelor over clopidogrel as part of the dual antiplatelet therapy (DAPT) after ST-segment elevation myocardial infarction (STEMI), irrespective of final management strategy. The aim of this multicenter prospective cohort study was to examine the efficacy and safety of bivalirudin with background ticagrelor and aspirin therapy in patients with STEMI undergoing primary percutaneous coronary intervention (PPCI).MethodsA total of 800 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…A, Univariate logistic regression analysis 95% CI ------------------------------------------------- ------------------------------------------------- aspirin and ticagrelor, bivalirudin reduces the incidence of NACEs compared with heparin (23). Moreover, another study indicated that in patients with STEMI who undergo PCI, bivalirudin decreases all-cause mortality compared with heparin (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A, Univariate logistic regression analysis 95% CI ------------------------------------------------- ------------------------------------------------- aspirin and ticagrelor, bivalirudin reduces the incidence of NACEs compared with heparin (23). Moreover, another study indicated that in patients with STEMI who undergo PCI, bivalirudin decreases all-cause mortality compared with heparin (24).…”
Section: Discussionmentioning
confidence: 99%
“…---------------------------------------- ---------------------------------------- artery disease complicated by diabetes who undergo PCI (14). Another study disclosed that the incidence of MACCEs does not vary between bivalirudin and the unfractionated heparin in patients with STEMI undergoing primary PCI (23). Moreover, in female patients with acute myocardial infarction who undergo emergency PCI, no discrepancy is observed in the incidence of MACCEs between bivalirudin and heparin (28).…”
Section: Discussionmentioning
confidence: 99%